Main right hepatic duct entering the cystic duct: a case report - Toshiya Abe; Shinichiro Ito; Yoshikazu Kaneda; Ryuichiro Suto; Shinji Noshima (Surgical Case Reports)
Abstract Background Risk factors for bile duct injury in laparoscopic cholecystectomy include severe inflammation at Calot’s triangle and aberrant bile duct variations. Knowledge of the various biliary anomalies and early identification may therefore assist in decreasing the rate of bile duct injury. Case presentation A 65-year-old woman was admitted with right hypochondrial pain and high fever. A diagnosis of acute calculous cholecystitis was made by radiological imaging. Magnetic resonance cholangiopancreatography revealed that the confluence of the right and left hepatic duct was unclear. Intraoperatively, the procedure was converted from a laparoscopic cholecystectomy to laparotomy because of unclear anatomy of the cystic duct with severe inflammation at Calot’s triangle. Furthermore, intraoperative cholangiography from Hartmann’s pouch showed the main right hepatic duct entering the cystic duct. Subtotal cholecystectomy was performed to avoid injuring the right hepatic duct. Conclusion Although an aberrant hepatic duct entering the cystic duct is not uncommon, the main right hepatic duct infiltrating the cystic duct is extremely rare. Preoperative and intraoperative evaluation of the biliary duct and awareness of aberrant biliary duct variations is important in preventing bile duct injury.